Pelatihan Pembuatan Laporan Akuntansi Perpajakan Pada Forum Pengusaha Kuliner Jogja - Suwandi, Eko Darmawan (LP3M Universitas Putra Bangsa, 2022)
The target to be achieved in this service program is to help make tax accounting reports for UMKM who are members of the